Atividade rizosférica de solo tratado com herbicida durante processo de remediação por Stizolobium aterrimum - Dos Santos, Edson Aparecido [UNESP]; Costa, Mauricio Dutra; Ferreira, Lino Roberto; Dos Reis, Marcelo Rodrigues; França, André Cabral; Dos Santos, José Barbosa (FapUNIFESP (SciELO), 2010)
This study aimed to evaluate the soil microbiota activity associated to S. aterrimum rhizosphere, during the phytoremediation process of a soil contaminated with trifloxysulfuron-sodium. S. aterrimum was cultivated in vases (6, 0 L) filled with soil, after trifloxysulfuron-sodium, at 7.5 g ha -1, was applied or not. Every 15 days after sowing (DAS), rhizospheric soil was collected for soil microbial respiration (amount of evolved CO 2) and microbial biomass carbon (MBC) analysis. To determine herbicide residues in the soil samples, after phytoremediation, Sorghum bicolor L. was cultivated as an indicator species, in addition to high performance liquid chromatography (HPLC) analysis. The microbiota associated to S. aterrimum rhizosphere showed to be sensitive to trifloxysulfuron-sodium and may be used as a microbiological indicator of disturbances caused by this herbicide in the environment. Regarding time for remediation, 45 days of development is enough for S. aterrimum to reduce residual trifloxysulfuron- sodium to a level not able to cause toxicity to the indicator plant.
Rhizosphere activity of soil treated with herbicide during remediation process by Stizolobium aterrimum
Keywords: Microbial biomass; Microbiological indicator; Phytoremediation; Sorghum bicolor; Stizolobium